Consequence of Diverse Nitrogen Levels on Leaf Pigments in Five Rice Genotypes Under Field Emergent Circumstances - Singh, Hukum; Verma, Amit; Krishnamoorthy, M.; Shukla, Alok (International Journal of Bio-resource and Stress Management, 2010)
The paper assesses the effect of dissimilar nitrogen levels on chlorophyll a, b, a/b, a+b and carotenoids content in assorted rice genotypes growing in field situation. The experiment was conducted throughout kharif season in 2008 and 2009. Five rice genotypes specifically KRH-2, Vasumati, Kasturi, Tulsi and Krishna Hamsa were taken as investigational material and urea was taken as a nitrogen source. The pigments content were anticipated at the instance of active tillering (AT) and flowering stage (FS). The pigments value was increased simultaneously with N levels and highest value was calculated at AT than FS. Chlorophyll a/b was increased after AT stage. Chlorophyll a was recorded higher for KRH-2 (AT) and Kasturi (FS), lower for Tulsi (AT) and Vasumati (FS). Chlorophyll b content was recorded greatest for Tulsi (AT) and Kasturi (FS) while minimum for Krishna Hamsa (AT) and Vasumati (FS). The upper limit of Chlorophyll a/b content was considered for Krishna Hamsa and Vasumati at AT and FS, although lower limit for Kasturi at same stage. Chlorophyll a+b content was calculated uppermost for KRH-2 (AT) and Kasturi (FS) whereas lowermost for Vasumati at both stages. Carotenoids contents were also drastically increased up to topmost N level and upper limit was recorded for KRH-2 and slighter for Vasumati at identical stage.